Evaluation of Different Date Palm Varieties and Pheromone Traps Against Red Palm Weevil (Rhynchophorus ferrugineus) in Sindh - Shar, Muhammad Usman; Rustamani, Maqsood Anwar; Nizamani, Shafi Muhammad; Buriro, Abdul Sattar; Bhutto, Liaquat Ali; Lodhi, Abdul Mubeen (Journal of Basic & Applied Sciences, 2012)
In a two-year study ten commercial date palm varieties were evaluated. The varieties showed varying response to Rhynchophorus ferrugineus Oliv; some varieties suffered heavy infestation while others indicated tolerance against R. ferrugineus. The most tolerant varieties with less infestation percentage against R. ferrugineus were Muzawati (8%) followed by Pathri (12%), Thothar (15%), Khar and Shakri (16%) respectively. The varieties which suffered high infestation rate were Karbalain, Dhedhi, Fasli, Aseel and Eidan Shah. To control the R. ferrugineus infestation pheromone trapping system was used. Significantly more R. ferrugineus (18-21) adults were captured during the 1st, 2nd, 3rd week of July and 2nd week of June. The studies conducted will be helpful in survey and control of R. ferrugineus infestation in Khairpur District of Sindh province.